The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1371/journal.pone.0141664
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Kiwifruit (Actinidia chinensis) Bark in Response to Armoured Scale Insect (Hemiberlesia lataniae) Feeding

Abstract: The kiwifruit cultivar Actinidia chinensis ‘Hort16A’ is resistant to the polyphagous armoured scale insect pest Hemiberlesia lataniae (Hemiptera: Diaspididae). A cDNA microarray consisting of 17,512 unigenes selected from over 132,000 expressed sequence tags (ESTs) was used to measure the transcriptomic profile of the A. chinensis ‘Hort16A’ canes in response to a controlled infestation of H. lataniae. After 2 days, 272 transcripts were differentially expressed. After 7 days, 5,284 (30%) transcripts were differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 72 publications
0
28
0
Order By: Relevance
“…In addition, hydrolysed phenolics of ‘Hort16A’ were more fungitoxic than those from ‘Hayward,’ which correlated positively with greater resistance of ‘Hort16A’ than ‘Hayward’ to Botrytis cinerea and Sclerotinia sclerotiorum infections ( Reglinski et al, 2002 ; Wurms et al, 2003 ; Wurms, 2005 ). The same β-1,3-glucosidase transcript that was analyzed in the current study has also been implicated in ‘Hort16A’ defense against scale insects ( Hill et al, 2015 ). In support of these molecular and biochemical findings, a proteomic study of ‘Hayward’ leaf colonization by Psa showed elevated expression of two beta-1,3-glucosidase isoforms 3 days after inoculation compared with a water control ( Petriccione et al, 2014 ).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In addition, hydrolysed phenolics of ‘Hort16A’ were more fungitoxic than those from ‘Hayward,’ which correlated positively with greater resistance of ‘Hort16A’ than ‘Hayward’ to Botrytis cinerea and Sclerotinia sclerotiorum infections ( Reglinski et al, 2002 ; Wurms et al, 2003 ; Wurms, 2005 ). The same β-1,3-glucosidase transcript that was analyzed in the current study has also been implicated in ‘Hort16A’ defense against scale insects ( Hill et al, 2015 ). In support of these molecular and biochemical findings, a proteomic study of ‘Hayward’ leaf colonization by Psa showed elevated expression of two beta-1,3-glucosidase isoforms 3 days after inoculation compared with a water control ( Petriccione et al, 2014 ).…”
Section: Discussionmentioning
confidence: 68%
“…The basal transcript level in untreated plants was then used as a further reference point for all calculations and is referred to with the value 1. Choice of GoIs was based upon their putative involvement in kiwifruit resistance against other important pests and diseases ( Wurms, 2005 ; Reglinski et al, 2010 ; Wurms et al, 2011 ; Hill et al, 2015 ), as well as preliminary qPCR studies of kiwifruit responses to Psa ( Wurms et al, 2013 ; Cellini et al, 2014 ), and a next generation sequencing study of the ‘Hort16A’/Psa interaction (A. Allan, PFR, New Zealand, unpublished data). Published studies of commonly used markers of hormonal pathways ( Suza and Staswick, 2008 ; Ding et al, 2009 ; Pieterse et al, 2009 , 2012 ; Sanchez-Vallet et al, 2012 ; Wasternack and Hause, 2013 ; Meesters et al, 2014 ), and defense responses of other plants, most often Arabidopsis thaliana , to Pseudomonas syringae were also used to select GoI ( Lorenzo et al, 2004 ; Pré et al, 2008 ; Liu et al, 2009 ).…”
Section: Methodsmentioning
confidence: 99%
“…The strong response FLS2 to Psa in this experiment suggests that it is successfully recognising flg22 in Psa flagellin. Based on conserved patterns in its nucleotide sequence, CC-NBS-LRR is a putative kiwifruit R gene that has been seen to respond to scale-insect challenge (Hill et al 2015). Host R genes that are involved in ETI and the expression of CC-NBS-LRR are likely to be responding to Psa effectors in this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Genes of interest (GoI) were selected based on published studies on Psa (Petriccione et al 2013;Cellini et al 2014;Petriccione et al 2014) and other kiwifruit-pathogen interactions (Wurms 2005;Wurms et al 2011b;Hill et al 2015), as well as an unpublished next generation sequencing study of temporal gene expression in kiwifruit with and without Psa infection (A. Allan, PFR, New Zealand, unpublished data). qPCR was performed in triplicate on cDNA from three biological replicates in 10 μL reactions containing 1 μL of a 10-fold dilution of the cDNA (for lowly expressed samples, runs were repeated with 2 μL), 1 μM of each of forward and reverse primers and 5 μL of Light Cycler® 480 SYBR Green 1 Master Mix (Roche Diagnostics GmbH, Mannheim, Germany, Product No.…”
Section: Quantitative Polymerase Chain Reaction (Qpcr)mentioning
confidence: 99%
See 1 more Smart Citation